TanshinoneⅡA protects acute lung injury in septic mice by regulating neutrophil extracellular traps - ZHANG Xiaohui; CHEN Congmin; DING Xinyun; DONG Xupeng; MA Yuqing (陆军军医大学学报, 2023)
Objective To observe the effect of tanshinoneⅡA (TanⅡA) on acute lung injury (ALI) in septic mice, and to explore its effect on neutrophil extracellular traps (NETs) and its possible mechanism. Methods A mouse model of sepsis was established by intraperitoneal injection of lipopolysaccharide (LPS) at a dose of 10 mg/kg. Thirty male C57BL/6 mice aged 6~8 weeks were randomly divided into 5 groups (n=6): Normal group (Nor group), LPS group, LPS+TanⅡA group (30 mg/kg TanⅡA was injected intraperitoneally 30 min before LPS injection), LPS+LY294002 group (pre-injection of 30 mg/kg LY294002), and LPS+DMSO group (pre-injection of the same amount of DMSO). At 12 h after modeling, the lung tissues were collected, lung coefficients were calculated, and pathological changes of lung tissue were observed with HE staining. ELISA was used to detect the levels of inflammatory factors IL-1β and IL-10 and NETs markers MPO-DNA complex and citrolinated histone H3 (Cit H3) in lung tissue. Western blotting was applied to detect the phosphorylation of the PI3K/AKT signaling pathway. Results Compared with the Nor group, the LPS group had an increased lung coefficient, significantly damaged lung tissue, increased levels of IL-1β (P < 0.05) and decreased level of IL-10 (P < 0.05), and elevated MPO-DNA complex and Cit H3 levels (P < 0.05) as well as the levels of p-PI3K and p-AKT (P < 0.05). While, the above conditions were much better in the LPS+TanⅡA group and the LPS+LY294002 group than the LPS group, with decreased lung coefficient, alleviated lung injury by HE staining and Smith scores, increased level of IL-1β and decreased IL-10 level in the lung tissue (P < 0.05), reduced levels of MPO-DNA complex and Cit H3 (P < 0.05) and p-PI3K and p-AKT (P < 0.05). Conclusion TanⅡA can alleviate sepsis-induced ALI, and its mechanism may be through inhibiting PI3K/AKT signaling pathway, regulating the level of NETs, and thus reducing the inflammatory response.